2019
DOI: 10.1055/a-0863-4355
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Profile of Curcumin and Nanocurcumin in Plasma, Ovary, and Other Tissues

Abstract: Background Curcumin is a natural diphenolic compound that is currently being investigated for various cancers, including ovarian cancer. Clinical application of curcumin has been limited due to its low solubility and bioavailability and rapid metabolism and degradation at physiological pH. Particle size is one factor that can affect the absorption process, which thus increases compound solubility and transport across the membrane. This study was conducted to determine the effects of modifying the particle siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In this study, the concentration of curcumin in renal tissue was determined at three different periods including 30 min, 1 h, 2 h after administration. The measured concentration of curcumin in renal tissue was very low when administrated on its own, which was consistent with the literatures ( Gutierres et al, 2015 ; Arozal et al, 2019 ). However, after combination with rhein, the level of curcumin in renal tissue was nearly doubled in 30 min after administration.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the concentration of curcumin in renal tissue was determined at three different periods including 30 min, 1 h, 2 h after administration. The measured concentration of curcumin in renal tissue was very low when administrated on its own, which was consistent with the literatures ( Gutierres et al, 2015 ; Arozal et al, 2019 ). However, after combination with rhein, the level of curcumin in renal tissue was nearly doubled in 30 min after administration.…”
Section: Resultssupporting
confidence: 92%
“…The concentration of rhein in renal tissue was increased more than 2-fold after co-administration (2.62 ± 0.70 μg/ml vs. 7.00 ± 0.65 μg/ml), indicating that combination with curcumin promoted the affinity of rhein with renal tissue. A previous study on the tissue distribution of curcumin showed that the concentration of curcumin in the heart, liver and kidney was extremely low ( Gutierres et al, 2015 ; Arozal et al, 2019 ). In this study, the concentration of curcumin in renal tissue was determined at three different periods including 30 min, 1 h, 2 h after administration.…”
Section: Resultsmentioning
confidence: 99%
“…The calibration curve of a standard solution was made with the final level of the analytes at 1, 2.5, 5, 10, 25, and 50 ng/mL. 24 The pharmacokinetic profiles were represented as mean and standard error (SE) from each group and were estimated through non-compartmental analysis. Pharmacokinetic parameters are calculated based on the curcumin concentration curve in plasma versus time.…”
Section: The Mucoadhesive Characteristics Of Curcumin Nanoparticlesmentioning
confidence: 99%
“…In addition, curcumin is stabilized in a solution with a pH < 6.5, and the degradation rate is significantly accelerated as the pH value of the solution increased. These properties of curcumin seriously limit its clinical application. As we know, liposomes have shown great potentials in drug delivery due to its drug-loading capacity, avoiding immune response, biodegradability, and biocompatibility. Liposomes are composed of a hydrophobic lipid bilayer and a hydrophilic inner aqueous chamber; lipophilic drugs can distribute in lipid bilayers in high percentages. Therefore, the liposomes as the carrier of curcumin have obvious advantages and several recent studies have confirmed this. Our previous study also found that the water-solubility and stability of curcumin were significantly improved after encapsulating it into liposomes …”
Section: Introductionmentioning
confidence: 95%
“…These properties of curcumin seriously limit its clinical application. 6 9 As we know, liposomes have shown great potentials in drug delivery due to its drug-loading capacity, avoiding immune response, biodegradability, and biocompatibility. 10 12 Liposomes are composed of a hydrophobic lipid bilayer and a hydrophilic inner aqueous chamber; lipophilic drugs can distribute in lipid bilayers in high percentages.…”
Section: Introductionmentioning
confidence: 99%